Infrared photodetectors - Seet, Wen Long (Nanyang Technological University, 2020)
In this project, the student will join a research team consisting of research staff and PhD students working on infrared photodetectors and assist them with characterizing and analysing photodetectors using equipment available in Nanyang Technological University. The dark and visible light response of Gallium Antimonide (GaSb) photoresistors will also be tested and the data obtained from the experiment are analysed. Lastly, the design, fabrication and characterization of middle wavelength infrared (MWIR) photodetector based on active Indium Arsenide Antimonide (InAs0.9Sb0.1) based hetero p-i-n structure grown on GaSb substrate will be presented. Within this structure, the active absorption layer is placed between thin layers of p-type and n-type quaternary material Aluminium Indium Arsenide Antomonide (AlInAsSb) and a heavily doped layer of Aluminium Gallium Antimonide (AlGaSb) is inserted to lower generation of dark current. Good lattice-matching between GaSb substrates and epitaxial layers is observed using high resolution x-ray diffraction (XRD). At 13 K, photoluminescence (PL) spectrum shows a full width at half maximum (FWHM) of approximately 29 meV, which shows the active absorption layers being of good quality. At 0 K, the bandgap energy of InAs0.9Sb0.1 is derived at approximately 0.322 eV by fitting from PL spectra at different temperatures. At room temperature, a rather flat responsivity of approximately 0.8 to 0.9 A/W over a wavelength range of roughly 2.1µm is demonstrated without antireflection (AR) coating. For room temperature operation under applied bias of -0.5 V, a detectivity of 8.9×108 cm.Hz1/2/W at 3.5µm is achieved.